The Impact of Teachers Pedagogical Competence in Building Students Social Interaction in Islamic Religious Education (PAI) Lessons at SMAN 4 Palangka Raya - Raudiyah, Noni; Wahdah, Nurul; Sapuadi, Sapuadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research aims to analyze the impact of teachers' pedagogical competence in building students' social interaction in Islamic Religious Education (PAI) subjects at SMAN 4 Palangka Raya. The pedagogical competence examined includes seven indicators: mastery of student characteristics, mastery of learning theory, curriculum development, implementation of educational learning, student potential development, communication, as well as learning assessment and evaluation. This research uses a qualitative narrative approach with one PAI teacher and 12 grade XI students as informants. Data collection techniques were conducted through in-depth interviews, observation, and documentation, which were then analyzed descriptively through data reduction, data presentation, and conclusion drawing processes. The research results show that teachers have attempted to apply pedagogical competence in the learning process, but its implementation is still limited to lecture methods, less varied use of learning media, and communication that is not yet fully two-way. This impacts the low active participation of students and limited development of healthy social interactions in the classroom. These findings confirm the importance of strengthening teachers' pedagogical competence through reflective training and the use of more inclusive learning strategies. This research contributes to the development of PAI learning approaches that not only focus on cognitive achievement but also encourage character building and students' social skills, which are essential in addressing educational challenges in the 21st century era.